2023
DOI: 10.1089/can.2021.0114
|View full text |Cite
|
Sign up to set email alerts
|

Observed Impact of Long-Term Consumption of Oral Cannabidiol on Liver Function in Healthy Adults

Abstract: Introduction: Previous studies have suggested that prescribed cannabidiol (CBD) products may cause elevations in liver tests (LT). This study compared the prevalence of elevated LT in an adult population self-administering CBD with the normal and general adult population prevalences. Materials and Methods: Adults 18–75 years of age across the United States taking CBD orally for a minimum of 30 days were recruited from 12 individual CBD product companies in this decentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 11 publications
(21 reference statements)
2
11
0
Order By: Relevance
“…It appears likely that non-clinical doses of commercially available CBD are unlikely to represent an appreciable risk to liver function. A similar sentiment was recently expressed in a large study of 839 healthy adults who regularly self-administered CBD (approximately 50 mg/day for 30 days); the authors speculated that the very few examples of unfavorable liver markers could be explained by co-existing medical conditions and/or the use of other supplements and medications [ 60 ].…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…It appears likely that non-clinical doses of commercially available CBD are unlikely to represent an appreciable risk to liver function. A similar sentiment was recently expressed in a large study of 839 healthy adults who regularly self-administered CBD (approximately 50 mg/day for 30 days); the authors speculated that the very few examples of unfavorable liver markers could be explained by co-existing medical conditions and/or the use of other supplements and medications [ 60 ].…”
Section: Discussionmentioning
confidence: 71%
“…In addition, in clinical trials of Epidiolex, indicators of liver dysfunction/damage were noted in four reports [ 56 , 57 , 58 , 59 ]. Alternatively, in a recent cross-sectional study of 839 habitual CBD users, no association was identified between CBD and multiple markers of liver health and function [ 60 ]. Furthermore, based on a review of the potential contribution of the endocannabinoid system to liver disease, others have called for CBD to be included in comprehensive treatments for liver disorders [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Transient CBD-related elevations of ALT and AST are commonly reported in clinical studies [ 40 , 46 , 47 , 48 , 50 , 54 , 56 ]. Transient transaminase abnormalities do not seem to be of critical long-term clinical significance for the liver as they tend to normalize following dose reduction or treatment discontinuation [ 57 , 58 ]. On the other hand, the second participant who experienced abnormally high elevated transaminases was a 62 years old white man with underling fatty liver disease with elevated levels of transaminases (ALT and AST) and blood glucose before the initiation of CBD treatment, along with alcohol binging which was not openly disclosed to the study team.…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that 50.3 mg/day of cannabidiol in the healthy population did not affect liver function. [20] Studies on cannabidiol use for PD treatment are limited, and most studies have a small sample size. Hence, this trial was conducted to examine the efficacy of a cannabidiol-enriched cannabis extraction product (CBDEP) on disease severity, QOL, functional performance, anxiety, depression, and renal and liver functions in patients with PD.…”
Section: Introductionmentioning
confidence: 99%
“…Another study showed that 50.3 mg/day of cannabidiol in the healthy population did not affect liver function. [ 20 ]…”
Section: Introductionmentioning
confidence: 99%